Biometaversia: Teknologi Pembelajaran Masa Depan dalam Memperkaya Pengetahuan Ketahanan Pangan dan Psikomotorik Siswa - Nova Izanah; Vina Risky Ayu Pratama; Intan Amalia Dini; Muhammad Mujamil; Sekar Kinasih; Rifda Nurapni Roudotun Nisa; Sulistiawati Sulistiawati; Aida Destiana Fitri (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2025)
Indonesia is one of the countries experiencing a food crisis. One of the aspects that makes Indonesia experience a food crisis is due to a decrease in food production due to limited agricultural land. The researcher developed Biometaversia media as an innovation in sustainable agriculture to educate high school students as one part of the community in hydroponic farming that can be done on limited land. In addition, another goal is to enrich students' knowledge about plant growth and development materials. This is done as an effort to create a food-secure society. This study was conducted on September 14, 2023 at SMA Negeri 1 Ciruas with a research population of 21 students in grade XI using the random sampling method. This research was conducted quantitatively with a quasi-experimental research method. Based on the results obtained, in the assessment of learning outcomes based on the average post-test score, an increased score of 66.79 from the pre-test score of 55.24 on the T Test which showed a significance value of 0.000 < 0.05, that there was a difference in student learning outcomes after being given treatment. Then in the assessment of psychomotor aspects (skills) at the time of hydroponic farming, the percentage of average scores with the very good category was obtained. This shows that students have skills in hydroponic farming because they are able to apply their hydroponic knowledge well.